How to effectively support export activity - Anna Fornalska-Skurczynska (Institute of Economic Research (IER), 2015)
Export is crucial for every economy. It influences the level of economic growth, balance of payment and social welfare among many others. Therefore increase in exports becomes one of the main objectives of each government. This raises the question of how to support export activity of the companies in order to ensure the expected increase in export. Approaches towards this problem differ significantly. The fact that this support is covered mainly from public funds raises the question of effectiveness of such assistance. The aim of this paper is to investigate whether to support export activity at all and if so how to do it effectively. To achieve the goal of the article the author analyzed both Polish and foreign literature, with special emphasis on the newest trade theories. Author analyzes secondary data describing factors that determine export activity, describe profile of a company becoming an exporter and investigates actual connection between offered support and increase in export activity.
Keywords: F10; F23; F40; 330; exporter; export activity; support; heterogeneous firms